Are the major European wine exporters able to price discriminate across their EU extra wine export destinations? - Imre Fertő; Jeremiás Máté Balogh (Hungarian Academy of Sciences, Institute of Economics, 2016)
In recent decades, New World has increased its wine export to European markets and became considerable in the global wine competition. However, the export share of traditional wine producers has decreased; Europe still remained market leader on world wine market. Moreover, the global wine market is characterised by progressively concentrated production, France, Italy and Spain accounting for about 50% of world wine production. Consequently, it is important to investigate what kind of pricing strategy the largest wine exporters of the world including France, Italy, Spain, Portugal and Germany can employ in their foreign wine export markets. The pricing behavior of five European wine exporters in their major destination markets is examined using a pricing-to-market (PTM) model for noncompetitive and exchange rate related pricing behaviour between 2000 and 2013. The results suggest that France and Italy were able to pursue price discrimination in many wine export destinations by contrast this advantage was not observable in a case of Spain, Portugal and Germany. The analysis of the asymmetric effects of exchange rates on wine export prices suggests that in many cases the depreciation of Australian, Hong Kong's; Singapore's dollar relating to euro had a greater impact than the appreciation while appreciation of Canadian and Singaporean dollar exceeded the effect of depreciation.
Keywords: Q17; F13; F14; 330; price discrimination; pricing to market (PTM); wine industry